PENGARUH PENERAPAN MODEL DISCOVERY TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR - Devianty Natalisa; Kartono Kartono; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to analyze the effect of the discovery model in thematic learning on thelearning outcomes of fifth grade students at SDN 09 Pontianak Barat.The research methodused is the experimental method. Quasi experimental research design with a nonequivalentcontrol group design. The population is all students of class V SDN 09 Pontianak Barat, 149students. Sampling using simple random sampling technique. The sample used was 61students consisting of 31 students of class VA as the experimental class and class VCof 30 students as the control class. The data collection technique is measurementwith a research instrument in the form of multiple choice tests.Based on thecalculations obtained, the average post-test learning outcomes of the experimental class78.13 with the average post-test learning outcomes of the control class of 70.30, then a tcountof 4.595 and ttable (=5%) and (dk=31+30-2=59) equal to 2.001, which means tcount (4.595)˃ ttable (2.001), then Ha is accepted. Based on the results of the calculation of the effect sizeobtained by 0.69 which includes medium criteria so that the discovery model gives an effectin thematic learning towards the learning outcomes of fifth grade students at SDN 09Pontianak Barat.Keywords: Influence, Discovery Model, Learning Outcomes, Thematic Learning.